2(3x-7)+2x=146

Simple and best practice solution for 2(3x-7)+2x=146 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-7)+2x=146 equation:


Simplifying
2(3x + -7) + 2x = 146

Reorder the terms:
2(-7 + 3x) + 2x = 146
(-7 * 2 + 3x * 2) + 2x = 146
(-14 + 6x) + 2x = 146

Combine like terms: 6x + 2x = 8x
-14 + 8x = 146

Solving
-14 + 8x = 146

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 8x = 146 + 14

Combine like terms: -14 + 14 = 0
0 + 8x = 146 + 14
8x = 146 + 14

Combine like terms: 146 + 14 = 160
8x = 160

Divide each side by '8'.
x = 20

Simplifying
x = 20

See similar equations:

| 4(1.5)= | | 18x^3=8x | | 11x^2=33x^3 | | 7b=3b(b+45) | | 17=4(x+3) | | 11x=33x | | -x+9=29 | | 3x+7x-4=2 | | X-7.6=-6.9 | | 3t-t-4=t-4 | | 165=20-y | | cos(5x)=.5 | | x^2-rad(3x)-6=0 | | 8x+16-6x-12=2x+6 | | 11f+2(f+1)=5f-6 | | 2(x+60)-((x+50)+60)=210 | | 29x=29x | | 100=4x+3y+0.1z | | -4p+4(1+2p)=-38-3p | | x^4+3x^3+3x^2+3x=0 | | 5x^2+3x-2y^2-3y-1=0 | | -4-(13x+6)+17=2+x-(14x-5) | | -4-(13x+6)+17=2 | | 9(3n+2)=8(8n+1)+8 | | 0=8x^2-42x+45 | | 5x+7=12-x | | -5u^2+21u+20=0 | | 2(6a-1)-(2a-3)+3(7a-5)= | | -6(7x-6)+3=-42x+39 | | -3(1-2x)=15 | | 6x+9=12x-15 | | -6(7x-6)+3=42x+39 |

Equations solver categories